Determinantes do desempenho financeiro dos municípios paulistas - Calife, Flávio Estévez (2006)
The aim of this research is to evaluate the deteminants of municipal fiscal performance in the state of São Paulo and its influence in the municipal creditworthiness during the years of 1997 and 2003. For this work we used panel data methods and logistic regression models. The criteria to be considered for the classification of the states and cities in accordance to its financial fiscal performance follows Lei complementar nº 089/97 from Finance Ministery. After the division of the cities in categories of performance the research analyzes the factors that affect the inclusion of a city in a category of financial performance. Variable tested are those used for the rating agencies, considered the institutions that better evaluate municipal financial performance. As subnacional governments ratings do not exist in Brazil, and as the agencies do not divulge its criteria of classification openly, we appeal to the literature that tries to reproduce agencies ratings, and from this literature we select our variables. Rating agencies consider economic, fiscal, indebtedness and administrative factors to determine financial performance of a municipality. Those variables are not available for every year so we decided to use cross section analysis for years 2000 and 2001. To improve the analysis of the results, we used added data (whole sample) and disaggregated data for population.